REKONSTRUKSI RASA BANGGA TERHADAP TRADISI DAERAH MELALUI PEMBELAJARAN BERBASIS LINGKUNGAN - Rachmat Panca Putera; Vella Nur Fatmawati; Shinta Septiana Pratiwi; Dinda Meividiana (CV JK Riset Publishing Group, 2025)
The weakening of students’ pride in local traditions has become a critical issue in primary education amid the pressures of cultural globalization. Cultural learning that is predominantly textual and symbolic has proven insufficient in fostering emotional attachment and cultural identity among students. This study aims to examine the role of environment-based learning in reconstructing students’ pride in local traditions among third- and fifth-grade students at MI Muhammadiyah Sidobasuki. A qualitative approach with a descriptive-interpretative design was employed. Data were collected through classroom observations, in-depth interviews with teachers and students, and documentation of environment-based learning activities. The data were analyzed thematically, with credibility ensured through source and technique triangulation. The findings indicate that environment-based learning facilitates a gradual reconstruction of pride in local traditions. Among third-grade students, reconstruction is reflected in increased interest and affective responses toward local traditions through concrete learning experiences. In contrast, fifth-grade students demonstrate a more reflective understanding, perceiving local traditions as an integral part of cultural identity and a collective heritage that should be preserved. This study concludes that environment-based learning is an effective contextual pedagogical strategy for fostering cultural pride from an early age. The findings contribute to the development of culturally responsive learning practices in primary education, particularly in strengthening students’ cultural identity through meaningful engagement with their local environment.